Application of ameliorant on the growth and product of pakchong (Pennisetum purpureum cv Thailand) in post-tin mining land - Lestari, Tri; Syazili, Ahmad; Pratama, Deni (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
Tin mining activities on Bangka Island cause the land to become nutrient-poor. Post-tin mining land use was done by adding ameliorant and cultivating pakchong grass. This research aimed to see the growth and yield of pakchong grass in post-tin mining land by applying mycorrhiza, biosaka and NPK fertilizer. This research was carried out on post-tin mining land in Dwi Makmur Village, Merawang District, Bangka Regency from March 2023 to July 2023. This research used a Randomized Group Factorial Design (RAKF) consisting of 2 treatment factors. The first factor was giving Mycorrhiza (B1) and Without Mycorrhiza (B2). The second factor was NPK 100% (P1), NPK 75% + Biosaka (P2) and NPK 50% + Biosaka (P3). The analysis of variance showed that mycorrhizal treatment had a significant effect on the number of leaves and tillers and had no significant effect on other treatments. Giving NPK + Biosaka treatment had a very significant effect on the number of leaves and had no significant effect on other treatments. The mycorrhiza  to pakchong plants grows better than without giving mycorrhiza. Giving a fertilizer to the 75% NPK + Biosaka (P2) treatment had no significant effect on the 100% NPK (P1) treatment. Giving mycorrhiza + NPK 75% (B1P2) results in higher plant height and leaf number compared to other treatments.